2020
DOI: 10.1101/2020.07.02.20144717
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers use and the risk of infection and clinical outcome of COVID-19: a comprehensive systematic review and meta-analysis

Abstract: Background The effect of using Angiotensin-converting enzyme inhibitors (ACEIs) and Angiotensin-receptor blockers (ARBs) on the risk of coronavirus disease 2019 (COVID-19) is a topic of recent debate. Although studies have examined the potential association between them, the results remain controversial. This study aims to determine the true effect of ACEI/ARBs use on the risk of infection and clinical outcome of COVID-19. Methods Five electronic databases (PubMed, Web of science, Cochrane library, Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Forty-six reviews (97.9%) compared COVID-19 related outcomes between ACEI/ARB users vs. non-users among patients with COVID-19 (4-6, 17-52, 54-60), one study (2.12%%) compared outcomes between ACEIs/ARBs users in patients with and without COVID-19 infection (53)), and 16 studies (34.0%) explored both (6, 19, 25-27, 40, 41, 43, 44, 48, 50, 51, 54, 56, 58, 60). Most of the included reviews were peer-reviewed publications (68.1%; n=32), whereas the remining 15 (31.9%) reviews were non-peer reviewed publications (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty-six reviews (97.9%) compared COVID-19 related outcomes between ACEI/ARB users vs. non-users among patients with COVID-19 (4-6, 17-52, 54-60), one study (2.12%%) compared outcomes between ACEIs/ARBs users in patients with and without COVID-19 infection (53)), and 16 studies (34.0%) explored both (6, 19, 25-27, 40, 41, 43, 44, 48, 50, 51, 54, 56, 58, 60). Most of the included reviews were peer-reviewed publications (68.1%; n=32), whereas the remining 15 (31.9%) reviews were non-peer reviewed publications (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 213 meta-analyses were conducted by the 47 reviews ( Supplementary file 4 ). In terms of number of COVID-19 related outcomes reported in each review, one outcome was reported by 13 reviews (27.7%) (18, 20, 21, 23, 24, 28, 29, 38, 39, 47, 52, 53, 61), two outcomes by 15 reviews (31.9%) (4, 17, 26, 31, 32, 34-37, 40, 42, 49, 54, 55, 58), three outcomes by 11 reviews (23.4%) (6, 22, 25, 27, 33, 44-46, 50, 56, 60) and 4-9 outcomes by eight reviews (17%) (19, 30, 41, 43, 48, 51, 57, 59). Overall, the 47 eligible reviews reported data on 18 unique pooled outcome estimates including death in 36 reviews, reviews (4, 6, 17-19, 22, 24, 25, 27, 30-39, 41-49, 54-56, 58-60), ICU admission in nine reviews (27, 28, 30, 41, 43, 48, 51, 56, 59), death/ICU admission as a composite outcome in 16 reviews (4, 20, 21, 23, 26, 29, 31, 32, 40, 41, 43, 45, 51, 55, 59), risk of acquiring COVID-19 infection in 15 reviews (19, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is only one study that showed that blocking AT1 receptors with losartan and inhibiting ACE2 with enalapril reduced the proportion of macrophages induced by Dengue fever virus (DENV2), a SARS-CoV-2-like RNA virus, suggesting a decrease in cell penetration by the virus and a role of ACE2 in Dengue virus infection [ 65 , 66 , 67 ]. The use of ACE inhibitors (ACEIs)/ARBs for COVID-19 patients does not lead to harmful outcomes and may even provide benefits and decrease mortality from COVID-19 [ 68 ].…”
Section: ⧉ Backgroundmentioning
confidence: 99%
“…Recent studies on the effects of RAAS inhibitors (ACEIs and ARBs) on the clinical outcomes of patients with COVID-19 have reported con icting results, ranging from a decrease in mortality [5,6], no effect [7][8][9][10] or even an increase in mortality [11]. Even previous meta-analysis studies had con icting ndings that reported either a decrease [12][13][14] or an increase [15] in mortality with RAAS inhibitors. These varying effects on mortality may not be caused by the drugs themselves and could be related to the underlying comorbidities that guided the antihypertensive drug selection (e.g.…”
Section: Introductionmentioning
confidence: 99%